Open Newton Contes Formula for Solving Linear Voltera Integro-Differential Equation of the First Order - Saleh, A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, some of numerical methods for solving first order linear Volterra IntegroDifferential Equations are presented. The numerical solution of these equations is obtained by using Open Newton Cotes formula. The Open Newton Cotes formula is applied to find the optimum solution for this equation. The computer program is written in (MATLAB) language (version 6)